Lexical Semantics for Terminology: An introduction, by Marie-Claude L’Homme - Haoda Feng; Hongying Xu (Ibérica)
The Terminology and Lexicography Research and Practice series by John Benjamins aims to offer readers in-depth studies that report on recent advances in the area of terminology and lexicography. The works collected for this book series cover a wide range of cutting-edge topics such as dynamics of terminologies (see e.g. Kageura, 2012) and terminological variation (see e.g. Daille, 2017), featuring a number of research methodologies such as philosophical, computational and cognitive approaches. Marie-Claude L’Homme’s book entitled Lexical Semantics for Terminology: An introduction in this series is very interesting, because it clarifies the interplay between lexical semantics and terminology, specifically including meaning and concept, term identification, polysemy, equivalence in terminology and so forth. In particular, this monograph highlights the robustness of corpus approaches and elucidates for readers how corpus data can be used to help facilitate quantitative and qualitative analyses within various lexico-semantic models, all of which is an innovative step towards the complement to knowledge-driven approaches. Therefore, the book under review would appeal to a broad spectrum of readership including terminologists, lexicographers, trainee and professional translators, corpus linguists, language researchers, and particularly those who show an interest in studies involving specialised terms.